Suscetibilidade magnética do solo e estimação da capacidade de suporte à aplicação de vinhaça - Peluco, Rafael Gonçalves [UNESP]; Júnior, José Marques [UNESP]; Siqueira, Diego Silva [UNESP]; Pereira, Gener Tadeu [UNESP]; Barbosa, Ronny Sobreira [UNESP]; Teixeira, Daniel de Bortoli [UNESP]; Adame, Cássia Rita [UNESP]; Cortez, Lucas Aguilar [UNESP] (FapUNIFESP (SciELO), 2013)
The objective of this work was to evaluate the magnetic susceptibility efficiency for estimating the support capacity of areas for vinasse application. Two hundred forty-one soil samples were collected from a 380-ha area, on which soil chemical properties, clay content, and magnetic susceptibility were determined. Vinasse requirement was calculated for each sample. Data were subjected to descriptive statistical analysis, and regression models were developed between magnetic susceptibility and the other evaluated attributes. The analysis of data spatial dependence was performed using geostatistics. Kriging maps and cross variograms were built in order to investigate the spatial correlation between soil magnetic susceptibility and studied attributes. Based on the map of vinasse requirement, on the soil classes, and on the kriging map, calculations were done for average vinasse dose and average soil support capacity, weighted by the area. Magnetic susceptibility has significant linear spatial correlation with recommended vinasse doses and soil support capacity for the application of this effluent, and it can be used as a pedotransfer function for indirect quantification of soil support capacity.

O objetivo deste trabalho foi avaliar a eficiência da suscetibilidade magnética do solo para estimar a capacidade de suporte de áreas à aplicação de vinhaça. Foram coletadas 241 amostras de solo, de uma área de 380 ha, nas quais foram determinados os atributos químicos, os teores de argila e a suscetibilidade magnética do solo. Foram calculadas as doses de vinhaça recomendadas para cada amostra. Os dados foram submetidos à análise estatística descritiva, e foram desenvolvidos modelos de regressão entre a suscetibilidade magnética e os outros atributos avaliados. A análise da dependência espacial dos dados foi feita com uso da geoestatística. Foram construídos mapas de krigagem e variogramas cruzados, para averiguar a correlação espacial entre a suscetibilidade magnética e os atributos estudados. Com base no mapa de recomendação de vinhaça, nas classes de solo e nos mapas de krigagem, foram calculadas as doses médias de vinhaça e as capacidades de suporte médias, ponderadas pela área. A suscetibilidade magnética apresenta correlação espacial linear significativa com as doses de vinhaça recomendadas e com a capacidade de suporte do solo à aplicação desse efluente, e pode ser utilizada como componente da função de pedotransferência, na quantificação indireta da capacidade de suporte.
Soil magnetic susceptibility for estimating the support capacity to vinasse application
Keywords: Geostatistics; Pedometrics; Pedotransfer.; Soil mapping